Interactions access. - Werner, Patricia K. (McGraw-Hill, 1997)
This text introduces, practices, and applies basic grammatical structures in everyday contexts. The conversational approach helps students use the grammar structures they are studying in real-life communication. Ideal for pre-beginning to beginning ESOL students.